The Effect of Task Technology Fit in Google Classroom Media on Learning Achievement in Higher Education: Goodhue and Thompson’s Theory - Rahman, Abdul; Hermawan, Yoni; Sartika, Sri Hardianti (Universitas Sebelas Maret, 2023)
The problems highlighted regarding student learning achievements varied each semester, before, during, and after the pandemic. This study, therefore, aims to determine the role of task technology fit of Google Classroom media using Goodhue and Thompson’s theory. The correspondence between assignments, students' abilities, and the functionality of educational technology evolves in tandem with technological advancements. The alignment between the outcomes, reflected in academic achievements at the end of the semester as a grade point average, needs to be supported by adequate facilities during the learning process. The quantitative method with an explanatory survey was used in this research. The population involved was students of the 2019 economics group at Siliwangi University, with a total sample of 264 students using a proportionate random sampling technique. Data collected through a closed questionnaire were then analyzed with regression techniques. The analysis results demonstrated a constant value (α) of 39.544. It implies that task technology fit (X) was constant or did not change, so learning achievement had a value of 39.544. Meanwhile, the regression coefficient for task technology fit (X) was 0.299, meaning that for every item, the value of task technology fit increased, and learning achievement increased by 0.299 units. The regression coefficient was positive since it illustrated a unidirectional influence between task technology fit and learning achievement. In conclusion, based on the implementation of task technology fit by Goodhue and Thompson’s theory, the task technology fit of Google Classroom media significantly affected learning achievement.